PENGARUH PERSEPSI HARGA, PROMOSI LANGSUNG DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN TABUNGAN EMAS PADA PT PEGADAIAN CABANG KUDUS - Yati, rumi; Hidayat, Yusmar Ardhi; -, Tavyastuti (Universitas Muria Kudus, 2023)
The decrease in the number of customers opening gold savings accounts during the past two years encourages PT Pegadaian in Kudus Branch Office to intensify direct promotion and service quality to improve customer purchase decisions. In addition, perceived price significantly affects customers opening gold savings. The purpose of this study was to analyze the effect of perceived price, direct promotion, and service quality on purchase decisions. This study used purposive sampling to obtain 100 respondents from customers with gold savings. This research implemented multiple regression for testing three hypotheses. This study revealed that: 1) perceived price had a negative impact on purchase decisions; and 2) Direct promotion had a positive impact on purchase decisions. 3) Service quality had a positive impact on the purchase decision. The perceived price has a negative impact on the purchase decision because the customer will save money if they have surplus income. PT Pegadaian of Kudus Branch should maintain direct promotions and improve service quality to improve purchase decisions in line with the increased number of customers opening accounts for gold savings. Finally, PT Pegadaian should focus on educating potential customers so they will have a good perception of gold saving advantages by performing direct promotions and maintaining service quality.